Interaction of antivirals with a heptameric bundle model of the p7 protein of hepatitis C virus - Dahl, Sophie L.; Kalita, Monoj Mon; Fischer, Wolfgang (Chemical biology and drug design, 2017)
A series of ligands are known experimentally to affect the infectivity cycle of the hepatitis C virus. The target protein for the ligands is proposed to be p7, a 63 amino acid polytopic channel-forming protein, with possibly two transmembrane domains. Protein p7 is found to assemble into functional oligomers of various sizes, depending on the genotype (GT). Nine ligands are docked to various sites of a computationally derived heptameric bundle of p7 of GT1a. The energy of interaction, here binding energy, is calculated using three different docking programs (Autodock, MOE, LeadIT). Three protein regions are defined to which the ligands are placed, the loop region and the site with the termini as well as the mid-region which is supposed to track poses inside the putative pore. A common feature is that the loop sites and poses either within the pore or at the intermonomer space of the bundle are preferred for all ligands with proposed binding energies smaller than −10 kJ/mol. BIT225, benzamine, amantadine, and NN-DNJ show good overall scoring.
Gesehen am 01.06.2018